Promoting low carbon behaviours through personalised information? Long-term evaluation of a carbon calculator interview. (September 2018) - Büchs, Milena; Bahaj, AbuBakr S.; Blunden, Luke; Bourikas, Leonidas; Falkingham, Jane; James, Patrick; Kamanda, Mamusu; Wu, Yue
Abstract: The UK needs to accelerate action to achieve its 80 per cent carbon reduction target by 2050 as it is otherwise in danger of lagging behind. A much discussed question in this context is whether voluntary behaviour change initiatives can make a significant contribution to reaching this target. While providing individuals with general information on climate change or low carbon action is increasingly seen as ineffective, some studies argue that personalised information has greater potential to encourage behaviour change. This mixed methods study examines this claim through a longitudinal field experiment which tested the effectiveness of a carbon calculator interview. It finds that the intervention significantly raised awareness of ways in which participants could reduce their carbon footprint. However, this increased awareness did not translate into measurable behaviour changes in relation to home energy and travel. Qualitative analysis shows that participants refer to infrastructural, social and psychological barriers to change. This indicates that more ambitious government and corporate action is required to speed up carbon reduction. Highlights: The provision of personalised information increased climate change awareness. Personalised information did not significantly affect long-term behaviours. Effective voluntary behaviour change interventions are time- and cost intensive. Important socio-technical and psychological barriers to carbon reduction persist. These barriers need to be addressed by more ambitious climate mitigation policies.